2001
DOI: 10.1002/ar.1112
|View full text |Cite
|
Sign up to set email alerts
|

Clonogenic analysis reveals reserve stem cells in postnatal mammals: I. Pluripotent mesenchymal stem cells

Abstract: Clonal populations of lineage-uncommitted pluripotent mesenchymal stem cells have been identified in prenatal avians and rodents. These cells reside in the connective tissue matrices of many organs and tissues. They demonstrate extended capabilities for selfrenewal and the ability to differentiate into multiple separate tissues within the mesodermal germ line. This study was designed to determine whether such cells are present in the connective tissues of postnatal mammals. This report describes a cell clone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 63 publications
1
94
0
Order By: Relevance
“…Postnatal Sprague-Dawley rats were euthanized using CO 2 inhalation, and the fleshy muscle bellies of the thigh and leg musculature were processed for stem cell isolation, cultivation, and cryopreservation (Young et al, 1991(Young et al, , 1998a(Young et al, , 2001aYoung, 2000.…”
Section: Cell Harvest and Culturementioning
confidence: 99%
See 4 more Smart Citations
“…Postnatal Sprague-Dawley rats were euthanized using CO 2 inhalation, and the fleshy muscle bellies of the thigh and leg musculature were processed for stem cell isolation, cultivation, and cryopreservation (Young et al, 1991(Young et al, , 1998a(Young et al, , 2001aYoung, 2000.…”
Section: Cell Harvest and Culturementioning
confidence: 99%
“…Previous cloning studies with prenatal chicks , prenatal mice (Rogers et al, 1995;Young et al, 1998a), and postnatal rats (Young et al, 2001a) revealed that repetitive singlecell clonogenic analysis could be achieved if individual cells were grown in medium preconditioned by highly proliferating cells of the same parental line. Therefore, the culture medium from stem cells undergoing postconfluence log-phase expansion was pooled, processed, and stored at -70 to 80°C.…”
Section: Repetitive Single-cell Clonogenic Analysismentioning
confidence: 99%
See 3 more Smart Citations